Embedding Plasmonic Metal into Heterointerface of MOFs‐Encapsulated Semiconductor Hollow Architecture for Boosting CO2 Photoreduction. Issue 17 (29th January 2023) - Mo, Weihao; Fan, Zhixin; Zhong, Shuxian; Chen, Wenbin; Hu, Lingxuan; Zhou, Hao; Zhao, Wei; Lin, Hongjun; Ge, Jing; Chen, Jianrong; Bai, Song
Abstract: Coupling hollow semiconductor with metal–organic frameworks (MOFs) holds great promise for constructing high‐efficient CO2 photoreduction systems. However, energy band mismatch between them makes it difficult to exert their advantages to maximize the overall photocatalytic efficiency, since that the blockage of desirable interfacial charge transfer gives rise to the enrichment of photoelectrons and CO2 molecules on the different locations. Herein, an interfacial engineering is presented to overcome this impediment, based on the insertion of plasmonic metal into the heterointerfaces between them, forming a stacked semiconductor/metal@MOF photocatalyst. Experimental observations and theoretical simulations validate the critical roles of embedded Au in maneuvering the charge separation/transfer and surface reaction: (i) bridges the photoelectron transfer from hollow CdS (H‐CdS) to ZIF‐8; (ii) produces hot electrons and shifts them to ZIF‐8; (iii) induces the formation of ZIF‐8 defects in promoting the CO2 adsorption/activation and transformation to CO with low energy barriers. Consequently, the as‐prepared H‐CdS/Au@ZIF‐8 with optimal ZIF‐8 thickness exhibits distinctly boosted activity and superb selectivity in CO production as compared with H‐CdS@ZIF‐8 and other counterparts. This work provides protocols to take full advantages of components involved for enhanced solar‐to‐chemical energy conversion efficiency of hybrid artificial photosynthetic systems through rationally harnessing the charge transfer between them. Abstract : An effective method of embedding plasmonic metal into semiconductor/metal‐organic framework (MOF) heterointerface is proposed, which not only circumvents the band mismatch and bridges the charge transfer between them, but also induces the formation of MOF defects and promotes CO2 adsorption, activation, and conversion.  As such, a stacked H‐CdS (hollow CdS)/Au@ZIF‐8 heterostructure is designed to fully exert the advantages of hollow semiconductors and MOFs for highly active and selective CO2 ‐to‐CO photoreduction.